Period Front Education Era Revolution Industry 4.0 Going To Society 5.0 - Permadi, Muhammad; Risnawati, Atin (Sekolah Tinggi Agama Islam Kuningan, 2025)
Education is an important element that must continue to develop in response to contemporary needs and societal developments. The rapid advancement of technology requires adaptation of educational systems to ensure that individuals can keep pace with this evolution. During the Industrial Revolution 4.0, education stressed the use of internet networks and information technology which were fundamental in the learning system. Blended learning, case-based learning, and hybrid learning were the dominant methodologies in this period. The emergence of the Society 5.0 period represents a transformation in several aspects of society, including education. This understanding facilitates the development of contemporary science that is adapted to meet human needs in accordance with current expectations. The Society 5.0 era is based on 21st century competencies which are closely related to rapid technological progress. This period offers efficiency and convenience, where technology helps and does not dominate, thus improving the quality of life to become more comfortable and prosperous.